Komitas in the Mirror of His Letters - Mnatsakanyan, Yeva (Bulletin of Yerevan University B: Philology, 2025)
Composer, musicologist, musician and collector of folklore, teacher, founder of the Armenian composer school Soghomon Soghomonyan, i.e., Komitas, is one of the national symbols, whose fate is perceived as the fate of the Armenian people. Many studies are devoted to him, but the mysterious image of Komitas continues to be in the center of attention of the Armenian and foreign researchers. The present article briefly analyzes the individual ideological and psychological aspects of Komitas’s letters, presents the deep philosophy reflected in them, where the vardapet appears as a son of his environment and country, as an exceptional musician, who has achieved worldwide recognition, and a highly educated personality with his inner movements and dramatic experiences. The purpose of the article is: a) to examine the multi-layered letters of Komitas as an exceptional tool for revealing the worldview and inner world of a person, b) to comprehend the key messages presented in the letters from the viewpoint of modern artistic consciousness, c) to reveal the process of intercultural communication on the example of Komitas’s letters, revealing the national and universal ideas embedded in them. The objectives of the study are the following: a) to study and comment on the encrypted signs concerning the coincidence of universal and national ideas in the letters of Komitas, b) to examine the phenomenon of the originality of the Armenian culture and musical art in the field of world cultural studies. The study of the material was conducted with the use of comparative-historical, descriptive and analytical methods. The pages of the letters do not fully reveal the secret of Komitas, but the following truth can be formulated: Komitas purified, transcribed to musical notes and created the majestic homeland of our song, whose impeccable and pure existence is undoubtedly a part of the Armenian history and philosophy of being.